Measuring Potential Efficiency Gains from Mergers of Italian First Instance Courts through Nonparametric Model. (January 2018) - Castro, Massimo Finocchiaro; Guccio, Calogero
In several countries, economic development has boosted the mobility of population, changing the distribution of litigation. Hence, the increasing difference between the new demand of legal services and the old judicial maps has increased processing time and backlog, therefore, badly affecting judiciary efficiency. These issues are particular relevant for the Italian judicial system because of the Italian government's proposal (decree n. 155/2012) of new judicial map of first instance courts. The courts' reorganization has been achieved through the horizontal merger of some courts and the abolition of all local courthouses. This article represents the first attempts at measuring the potential performance improvements achieved by the enforced reform. For this purpose, we compare the efficiency levels of Italian first instance courts in 2011 with those reached by the new judicial map. Our results show not negligible efficiency gains from the proposed mergers under the variable returns to scale technology assumption.